Low Threshold Telemedicine-based Opioid Treatment for Criminal Justice Involved Adults During the COVID-19 Pandemic: A Case Report. Issue 1 (11th January 2022) - Flavin, Lila; Tofighi, Babak; Krawczyk, Noa; Schatz, Daniel; McNeely, Jennifer; Butner, Jenna
Abstract : Criminal justice involved individuals have a high rate of opioid overdose death following release. In March 2020, New York City jails released over 1000 inmates due to concern of COVID-19 outbreaks in county jails. The closure of addiction treatment clinics further complicated efforts to expand access to medications for opioid use disorder among criminal justice involved adults. The New York City Health + Hospitals Virtual Buprenorphine Clinic established in March 2020 offered low-threshold telemedicine-based opioid treatment with buprenorphine-naloxone, specifically for criminal justice involved adults post-release. We describe a case report of the novel role of tele-conferencing for the provision of buprenorphine-naloxone for jail-released adults with opioid use disorder experiencing homelessness during the COVID-19 pandemic. The patient is a 49-year-old male with severe opioid use disorder released from New York City jail as part of its early release program. He then started using diverted buprenorphine-naloxone, and 1 month later a harm-reduction specialist at his temporary housing at a hotel referred him to an affiliated buprenorphine provider and then eventually to the New York City Health + Hospitals Virtual Buprenorphine Clinic, where he was continued on buprenorphine-naloxone, and was followed biweekly thereafter until being referred to an office-based opioid treatment program. For this patient, telemedicine-based opioid treatment offered a safe and feasible approach to accessing medication for opioid use disorder during the COVID-19 pandemic and following incarceration.